2015
DOI: 10.3389/fpls.2015.00030
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and proteomic analyses of leaves from the halophyte Tangut Nitraria reveals diverse response pathways critical for high salinity tolerance

Abstract: Soil salinization poses a serious threat to the environment and agricultural productivity worldwide. Studies on the physiological and molecular mechanisms of salinity tolerance in halophytic plants provide valuable information to enhance their salt tolerance. Tangut Nitraria is a widely distributed halophyte in saline–alkali soil in the northern areas of China. In this study, we used a proteomic approach to investigate the molecular pathways of the high salt tolerance of T. Nitraria. We analyzed the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
7
40
0
Order By: Relevance
“…Among the PSI core proteins, PsaA, PsaB, and PsaC [59] were decreased in alkaligrass (Figure S8C), barley ( Hordeum vulgare ) [60], and other halophytes [33,61]. The phosphorylation of PsaC was enhanced in alkaligrass at 24 HAT (Figure S8C), which has been reported in Arabidopsis, green algae ( Chlamydomonas reinhardtii ), and spikemoss ( Selaginella moellendorffii ) [23].…”
Section: Discussionmentioning
confidence: 60%
“…Among the PSI core proteins, PsaA, PsaB, and PsaC [59] were decreased in alkaligrass (Figure S8C), barley ( Hordeum vulgare ) [60], and other halophytes [33,61]. The phosphorylation of PsaC was enhanced in alkaligrass at 24 HAT (Figure S8C), which has been reported in Arabidopsis, green algae ( Chlamydomonas reinhardtii ), and spikemoss ( Selaginella moellendorffii ) [23].…”
Section: Discussionmentioning
confidence: 60%
“…Proteomics have been used as a useful tool for facilitating the comparison of complex mixtures of proteins, and it is now widely applied for exploring the molecular mechanisms of plants in response to environmental stresses (Lv et al, ). Recently, proteomics‐based technologies have been broadly employed to identify the proteins responsible for salinity tolerance in halophytes such as Suaeda corniculata (Pang, Zhang, Zang, Wei, & Yan, ), Halogeton glomeratus (Wang, Yao, Li, Meng, & Ma, ), and Tangut nitraria (Cheng et al, ), which has accelerated the understanding of the protein‐level molecular mechanisms of plant salt tolerance. However, the effect of AMF on salinity stress tolerance in halophytes has not been explored using proteomics.…”
Section: Introductionmentioning
confidence: 99%
“…These results were similar to the findings of Maršálová et al, (2016) in which they identified in salt tolerant species of Hordeum vulagre. In contrast, Cheng et al, (2015) found that magnesium chelatase decreased in salt stressed plants of Tangut nitraria. Only one protein UDP-glucose for carbohydrate anabolism was differentially expressed in salt stressed canola cultivars.…”
Section: Discussionmentioning
confidence: 82%